The school routine in the Brazilian journal in educational studies (1984-2014) - Avelino, Wagner Feitosa [UNESP]; Salles, Leila Maria Ferreira [UNESP] (My University, 2015)
The objective of this present research aims to investigate what the authors have written and analyzed about the school routine in Brazil between 1984-2014 through the publications published by the Revista Brasileira de Estudos e Pedagógicos (Journal of Pedagogical Studies) magazine. Thus, a mapping and analysis of the articles - published by the mentioned magazine – was done, related to the theme. A total of 79 articles were selected for this work. They indicate a fact: the importance that the researchers have given to the study of school routine. The analysis shows that the studies dealt primarily with Elementary Education and Teaching Practice with a focus on the teachers.
Keywords: Documental research; Magazines; School routine; Teachers training